Grape seed extract role against carbimazole action on thyroid gland and lipid profile in male rats. - Jassem AL-Naely, Ahmed; Kareem Wali, Jameel; Turki Shattnan, Dalal (Al-Qadisiyah Journal of Pure Science, 2018)
The aim of the current study is to identify the role of grape seed extract in thyroid gland and lipid profile disorders induced by Carbimazole 30 mg/kg.b.w. The experience including 40 male rats randomly divided into five groups each group consist of 8 animals, grape seed extract used by dose 150mg/kg daily for the duration of the 30-day study period. Results showed that the animals treated with carbimazole had a significant decrease(P<0.05) in the concentration of thyroid hormones and increase TSH compared with their normal range level in the control group and the rest of the experimental groups, While groups in which grape seed extract(GSE) interferes with drug showed improvement in thyroid hormones level closer to normal range in control group. Also the results showed significant increase (P<0.05) in TC, TG HDL, vLDL and significant decrease in LDL in carbimazole group, in addition to damage in thyroid tissue. On the other hand animals treated by both grape seed extract (GSE) and drug showed significant improvement(P<0.05) in TC, TG, HDL, vLDL, LDL and thyroid tissue compared with groups treated with drug only. It was concluded from this study that grape seeds extract had protective role against damage caused by carbimazole.